2016
DOI: 10.1038/srep27126
|View full text |Cite
|
Sign up to set email alerts
|

Extensive coronavirus-induced membrane rearrangements are not a determinant of pathogenicity

Abstract: Positive-strand RNA (+RNA) viruses rearrange cellular membranes during replication, possibly in order to concentrate and arrange viral replication machinery for efficient viral RNA synthesis. Our previous work showed that in addition to the conserved coronavirus double membrane vesicles (DMVs), Beau-R, an apathogenic strain of avian Gammacoronavirus infectious bronchitis virus (IBV), induces regions of ER that are zippered together and tethered open-necked double membrane spherules that resemble replication or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 56 publications
0
32
0
Order By: Relevance
“…This result was replicated in several continuous cell lines and primary cells. Furthermore, a survey of Infectious bronchitis virus revealed that one high-pathogenicity strain produced abnormally low numbers of double-membrane spherules, while still producing an equivalent amount of RNA to a vaccine strain (Maier et al, 2016). These results suggest that whatever their purpose, coronavirus replicative organelles display a surprising degree of structural plasticity without necessarily impairing RNA production, pathogenicity or competitive fitness.…”
Section: Dmos and Viral Replication Fitnessmentioning
confidence: 97%
See 1 more Smart Citation
“…This result was replicated in several continuous cell lines and primary cells. Furthermore, a survey of Infectious bronchitis virus revealed that one high-pathogenicity strain produced abnormally low numbers of double-membrane spherules, while still producing an equivalent amount of RNA to a vaccine strain (Maier et al, 2016). These results suggest that whatever their purpose, coronavirus replicative organelles display a surprising degree of structural plasticity without necessarily impairing RNA production, pathogenicity or competitive fitness.…”
Section: Dmos and Viral Replication Fitnessmentioning
confidence: 97%
“…Regions of these pairedmembrane structures have been given a variety of names in the literature, including double-membrane vesicles (DMVs), convoluted membranes, spherules, zippered endoplasmic reticulum, but it is not clear whether the different parts of the organelle have different functions. Furthermore, recent studies (Al-Mulla et al, 2014;Maier et al, 2016) suggest that there may be considerable plasticity and overlap among coronavirus paired membrane replicative structures. For this reason, it seems preferable to break with past practice of focussing on double-membrane vesicles in particular, to consider the double-membrane organelle (DMO) as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…However the interaction of these two nsps was insufficient in itself to trigger membrane rearrangement and host factors such as EDEM1 and OS9 of the ER-associated degradation system have been shown to be co-factors [77,78]. Despite them being a universal feature of CoVs the size and number of DMVs does not appear to correlate directly with viral fitness, at least when virus is grown at reduced temperatures [79] nor are they a determinant of pathogenicity [80]. For the γ CoV Infectious Bronchitis Virus (IBV), nsp4 was essential and sufficient to induce membrane pairing, recognized as extensive areas of membrane accumulation or small regions of paired membrane, but expression of nsp3, nsp4 and nsp6 was required for DMV production which, even then, was poor for strain BeauR and not seen at all for strain M41.…”
Section: Nonstructural Protein Interactionsmentioning
confidence: 99%
“…All coronaviruses induce the formation of DMVs. In addition, there are rearrangements of the endoplasmic reticulum (ER) to form either a branching network of membranes referred to as convoluted membranes (CM) found in Alpha - and Betacoronavirus infected cells [2023] or paired ER membranes referred to as zippered ER in Gammacoronavirus infectious bronchitis virus (IBV) infected cells identified in our previous work [24, 25]. Associated with the zippered ER in IBV infected cells are small double membrane spherules, not seen previously in cells infected with other coronaviruses.…”
Section: Introductionmentioning
confidence: 99%